2023
DOI: 10.1108/ijqss-11-2021-0160
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between students’ psychological capital, social-contextual factors and study-related outcomes – an empirical study from higher education in Norway

Abstract: Purpose This study aims to examine the relationships between students’ psychological capital (PsyCap), social-contextual factors and study-related outcomes. Social-contextual factors are represented by two education-related variables: academic support and peer support. Three study-related outcome variables are included, namely, study engagement, academic performance and student well-being. Design/methodology/approach Students from different higher education campuses and academic programs in Norway participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“… 65 Academic and Peer support positively impact the development of individual resources within student PsyCap, both separately and together, as they reflect students’ perceptions of supportive academic and peer environments, respectively. 53 Nielsen et al 78 also found that instructors’ encouragement helps students build their PsyCap. Thus, these findings deepen our comprehension of the affective antecedents of academic PsyCap, where both personal and family-social factors influence individual psychological capital, and in addition in teamwork, where harmonious team relationships are integral contributors to individuals’ psychological capital.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 65 Academic and Peer support positively impact the development of individual resources within student PsyCap, both separately and together, as they reflect students’ perceptions of supportive academic and peer environments, respectively. 53 Nielsen et al 78 also found that instructors’ encouragement helps students build their PsyCap. Thus, these findings deepen our comprehension of the affective antecedents of academic PsyCap, where both personal and family-social factors influence individual psychological capital, and in addition in teamwork, where harmonious team relationships are integral contributors to individuals’ psychological capital.…”
Section: Resultsmentioning
confidence: 99%
“…In academia, an increasing body of studies suggests that PsyCap has a beneficial influence on students’ outcomes. 53 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested a positive relationship between psychological capital and academic performance (Jafri, 2013). Psychological capital affects academic performance (Carmona-Halty et al, 2021;Slåtten et al, 2023). School psychological capital was associated with optimal academic outcomes (King and Caleon, 2021).…”
Section: Psychological Capital and Academic Performancementioning
confidence: 99%
“…Learning motivation, especially intrinsic motivation, is positively correlated with academic outcomes measured by scores or grades (Schunk et al, Liu et al 10.3389/fpsyg.2024.1357936 Frontiers in Psychology 02 frontiersin.org 2008; Lazowski and Hulleman, 2016;Alkış and Taşkaya Temizel, 2018); Emotional engagement is considered to directly affect learning outcomes or indirectly affect by shaping behavioral and cognitive engagement (Raver, 2002;Bierman et al, 2008;Liew et al, 2008;Engels et al, 2021;Hasnine et al, 2023). Psychological capital, as an individual's positive psychological state, leads to positive organizational behavior, and has a positive relationship with academic performance (Jafri, 2013;Khajavy et al, 2019;Carmona-Halty et al, 2021;King and Caleon, 2021;Slåtten et al, 2023). However, only limited research includes all three factors, although there is some study on interaction between two of these three factors.…”
Section: Introductionmentioning
confidence: 99%